22.7k views
2 votes
The functions f and g are defined as follows.

g(x) = -2x3-5
f(x) = - 4x + 2
Find f (6) and g(-3)
Simplify your answers as much as possible.

User Matzeri
by
6.1k points

1 Answer

0 votes

Answer:

f(6) = -22, and g(-3) = 49

Explanation:

f(x) = -4x + 2

f(6) = -4(6) + 2

f(6) = -24 + 2

f(6) = -22

I assume the 3 in g(x) = -2x3 -5 is cubed

g(-3) = -2(-3)^3 - 5

g(-3) = -2(-27) - 5

g(-3) = 54 - 5

g(-3) = 49

User Merril
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.